Ecological and archaeological consequences of ongoing, largely human‐mediated colonisation of endemic soft, shelly habitats by mangroves in a northern New Zealand embayment - John D. Booth; James J. Robinson; Reuben C. Booth; Robert S. Willoughby (New Zealand Journal of Marine and Freshwater Research, 2024)
Areal extent of native mangroves, Avicennia marina , has doubled in Bay of Islands since 1951. This expansion is widely attributed to deforestation and poor land‐use practices beginning in the late 1800s to early 1900s, and led to greatly transformed intertidal and supratidal habitats. One example has been the ecological isolation and crowding (sometimes, colonisation) by mangroves of shelly beaches, together with their associated ‘chenier‐like’ spits – themselves now among the rarest of New Zealand's inshore marine habitats, with only six still relatively intact ecologically out of at least 44 in the Bay of Islands. These shores were also where pre Contact Māori often gathered to harvest intertidal cockles Austrovenus stutchburyi and to fish, archaeological signatures typically becoming obscured once mangroves colonised upper shores. Although recent seaward intrusion by mangroves into the cockle habitat of the Parekura Bay study site appears to have been proportionately small, there may be potential for more as elevated levels of sedimentation persist. With wholesale mangrove removals demonstrably ineffective in re‐establishing original communities, the ongoing ecological and archaeological disruption of endemic soft, shelly contexts through largely human‐mediated mangrove colonisation might be curbed in certain situations through strategic, proactive removal of new mangrove recruits, particularly on expanding edges.